Equal affections - Leavitt, David (Weidenfeld & Nicholson, 1989)
Family matriarch Louise Cooper, mother of gay siblings April and Danny, suffers one medical malady after another, while Nat, her computer scientist husband, enjoys a longterm affair on the side. As Louise's condition deteriorates, tensions mount and family members attempt to define and justify their conflicting feelings
Keywords: Families; Mothers; Gays